2014
DOI: 10.1073/pnas.1323895111
|View full text |Cite
|
Sign up to set email alerts
|

Membrane adhesion dictates Golgi stacking and cisternal morphology

Abstract: Two classes of proteins that bind to each other and to Golgi membranes have been implicated in the adhesion of Golgi cisternae to each other to form their characteristic stacks: Golgi reassembly and stacking proteins 55 and 65 (GRASP55 and GRASP65) and Golgin of 45 kDa and Golgi matrix protein of 130 kDa. We report here that efficient stacking occurs in the absence of GRASP65/55 when either Golgin is overexpressed, as judged by quantitative electron microscopy. The Golgi stacks in these GRASP-deficient HeLa ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 29 publications
5
88
2
Order By: Relevance
“…Thus, membrane adhesion basically acts as the flattening force. Lee et al (11) reported that a knockdown of adhesion proteins caused a swelling of Golgi cisternae. In contrast, our simulations indicated that stronger adhesion affecting the membrane morphology prevents the formation of fine Golgi-like strictures (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, membrane adhesion basically acts as the flattening force. Lee et al (11) reported that a knockdown of adhesion proteins caused a swelling of Golgi cisternae. In contrast, our simulations indicated that stronger adhesion affecting the membrane morphology prevents the formation of fine Golgi-like strictures (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Via the fragmentation, Golgi components completely decompose and lose their morphological characteristics such as the structural anisotropy and long-range coherence. In contrast, there are few reports of moderately decomposed states (11). Therefore, this all-or-none response is a fundamental characteristic of the Golgi architecture.…”
mentioning
confidence: 92%
“…It has been proposed that existence of either one or the other Golgi organization reflects the underlying differences in the organization of the endoplasmic reticulum (ER) exit sites: In P. pastoris, where the Golgi forms stacks, ER exit sites are discrete, confined at specific ER locales, while in S. cerevisiae, where the Golgi is dispersed, vesicles bud throughout the ER network (Rossanese et al 1999). Golgins, large coiled-coil proteins at Golgi's cytoplasmic surface, together with Golgi ReAssembly Stacking Proteins (GRASPs) also have been implicated in Golgi stacking, as well as in Golgi ribbon formation in mammalian cells (Wang et al 2003, Munro 2011a, Lee et al 2014, Veenendaal et al 2014, while these proteins are thought to contribute to the specificity of membrane traffic to the Golgi in yeast but also in higher eukaryotes (Behnia et al 2007, Wong andMunro 2014). Nevertheless, the exact mechanism by which stacking is achieved is not definitively understood and even less clear remains the role this Golgi organization plays in protein secretion or other cellular function (Emr et al 2009).…”
Section: Filamentous Fungal Golgi In Electron Micrographsmentioning
confidence: 99%
“…The unlinking of the Golgi ribbon in G2 is controlled by the protein CtBP1 (also known as, and hereafter referred to as BARS) (Colanzi et al, 2007) and by the Golgi stacking factors GRASP55 (also known as GORASP2) and GRASP65 (also known as GORASP1) (Lee et al, 2014). In this context, BARS stimulates the fission-mediated cleavage of the tubules that connect the stacks of the Golgi ribbon (Carcedo et al, 2004;Corda et al, 2006;Colanzi et al, 2007), and GRASP55 and GRASP65 are involved in the maintenance of the ribbon structure (Puthenveedu and Linstedt, 2004;Sutterlin et al, 2005;Tang et al, 2012;Jarvela and Linstedt, 2014).…”
Section: Introductionmentioning
confidence: 99%